PENINGKATAN KEMAMPUAN MEMBACA RITMIS MENGGUNAKAN LAGU MODEL PADA SISWA KELAS VII SMPN 3 TELUK KERAMAT - Nugroho, Muhammad Arvin; Istiandini, Winda; Muniir, Asfar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe background of this study was the lack of students' abilities in reading the music rhythm in playing a similar music ensemble. In the learning process, the teacher still used the conventional teaching method in the form of lectures. The process and results of improving rhythmic reading skills in 7th-grade students of SMP 3 Teluk Keramat on similar musical ensemble material using a model song. The theories used in this study were Learning, Music, Rhythmic Reading Ability, Music ensembles, Learning Media, Model Songs. Classroom Action Research with the descriptive method and qualitative approach were used as the form of the research. Data were analyzed through the stages of data reduction, data presentation, and verification in the form of conclusions from the results of student presentations in cycles 1 and 2. The data were validated by using the triangulation technique by checking the data to the same source with different techniques. The findings showed that there was an improvement in students’ rhythmic reading abilities from the learning process conducted. After the learning the students’ abilities were improved respectively from 61.89, 67.80 to 86.11. Therefore, students’ abilities in rhythmic reading towards similar musical ensemble can be improved by using model songs media.Keywords: model songs, media, rhythmic reading, student’ abilities